Determinants Affecting Consumer Purchase Decisions in The New Normal Era - Beby Karina Fawzeea Sembiring; Endang Sulistya Rini; Yeni Absah (Journal of International Conference Proceedings, 2021)
The purpose of this study is to determine the effect of product quality on purchasing decisions in the new normal era, to determine the effect of price on purchasing decisions in the new normal era, to determine the effect of promotion on purchasing decisions in the new normal era, to determine the effect of product quality price and promotion on purchasing decisions in the new normal era. The population in this study were Shopee users in the city of Medan. The data analysis tools used are descriptive statistics and SPSS statistics. The results showed that product quality price and promotion partially had a positive and significant effect on purchasing decisions. Simultaneously it is also known that product quality, price and promotion simultaneously have a positive and significant effect on purchasing decisions.